PlasmoGEM, a database supporting a community resource for large-scale experimental genetics in malaria parasites. Issue Volume 43:Issue D1(2015) (12th December 2015) - Schwach, Frank; Bushell, Ellen; Gomes, Ana Rita; Anar, Burcu; Girling, Gareth; Herd, Colin; Rayner, Julian C.; Billker, Oliver
Abstract : The Plasmodium Genetic Modification ( Plasmo GEM) database (http://plasmogem.sanger.ac.uk ) provides access to a resource of modular, versatile and adaptable vectors for genome modification of Plasmodium spp. parasites. Plasmo GEM currently consists of >2000 plasmids designed to modify the genome of Plasmodium berghei, a malaria parasite of rodents, which can be requested by non-profit research organisations free of charge. Plasmo GEM vectors are designed with long homology arms for efficient genome integration and carry gene specific barcodes to identify individual mutants. They can be used for a wide array of applications, including protein localisation, gene interaction studies and high-throughput genetic screens. The vector production pipeline is supported by a custom software suite that automates both the vector design process and quality control by full-length sequencing of the finished vectors. The Plasmo GEM web interface allows users to search a database of finished knock-out and gene tagging vectors, view details of their designs, download vector sequence in different formats and view available quality control data as well as suggested genotyping strategies. We also make gDNA library clones and intermediate vectors available for researchers to produce vectors for themselves.